2017 ACM/IEEE International Symposium on Empirical Software Engineering and Measurement (ESEM) 2017
DOI: 10.1109/esem.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Graphical vs. Tabular Notations for Risk Models: On the Role of Textual Labels and Complexity

Abstract: Abstract[Background] Security risk assessment methods in industry mostly use a tabular notation to represent the assessment results whilst academic works advocate graphical methods. Experiments with MSc students showed that the tabular notation is better than an iconic graphical notation for the comprehension of security risks.[Aim] We investigate whether the availability of textual labels and terse UML-style notation could improve comprehensibility. [Method] We report the results of an online comprehensibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 33 publications
1
11
1
Order By: Relevance
“…There are few significant difference and some similarities between this study and our previous works [23,25] which we summarize in Table 1. The main contribution of this work is studying how well tabular and graphical risk modeling notations support memorization of information about security risks.…”
Section: Related Worksupporting
confidence: 66%
See 4 more Smart Citations
“…There are few significant difference and some similarities between this study and our previous works [23,25] which we summarize in Table 1. The main contribution of this work is studying how well tabular and graphical risk modeling notations support memorization of information about security risks.…”
Section: Related Worksupporting
confidence: 66%
“…This study showed that supplementing a textual description of security decision problem with graphical representation improves risk perception and participants' confidence in decisions, but does not contribute to the comprehension of the problem or security investment decision. In our prior study [25] we also found that participants achieved better or equal comprehension of described risk scenarios with tabular and UML-based notations.…”
Section: Related Workmentioning
confidence: 66%
See 3 more Smart Citations